Evaluation of Blood Ordering Practice for Packed Red Blood Cells in A Tertiary Care Hospital - Thamarai, Selvi. N; Krishna, PrasanthB; Anusha, A.S; Rameejan, Begum (International Journal of Blood Transfusion, 2018)
Introduction: Blood is a valuable resource and blood transfusion is life saving in many situations. However blood transfusions carry the risk of transfusion transmitted infections, allergic reactions, hemolytic reactions and introduction of foreign antigens. So monitoring of blood transfusion practice is necessary for the rationale use of blood components. The aim of this study was to evaluate the appropriateness of blood ordering practice for Packed Red Blood Cells (PRBC) as per National Blood Transfusion Guidelines. Materials & Methods: The study was conducted in a tertiary care hospital in Tamilnadu. A total of 4236 blood request forms were analyzed over a period of 12 months. Number of units requested were noted and the appropriateness of the requested transfusion was assessed according to the National guidelines on transfusion 3. Request forms of neonates and children up to 18 years of age (in whom Transfusion guidelines are different) were excluded from the study. Cross match to Transfusion ratio (CT ratio) was also calculated. Results: A total of 4236 blood request forms were analyzed out of which 76.6 % (n=3246) were for PRBC, and hemoglobin values were mentioned in 68.8% (n=2235) and not mentioned in 31.2% (n=1011) of request forms. Anemia, surgery and bleeding were the most common indications for which transfusions were requested. There were 3246 PRBC requests out of which 53.5% (n=1736) requests were considered appropriate, 38.6% (n=1254) were considered inappropriate and 7.9% (n=256) requests could not be assessed due to inadequate details on Hemoglobin and clinical relevance. CT ratio was 1.5. Conclusion: In this study, it was noted that significant percentage (38.6%) of inappropriate PRBC transfusions were given and 7.9% forms could not be assessed due to inadequate investigation details. Regular audits and CMEs should be conducted in this hospital to rationalize the use of blood components.
Keywords: Transfusion appropriateness; PRBC.